A Self-report Home Environment Screening Tool for Determining Fall Risk in Iranian Older People - Elham Karimi; Afsoon Hassani Mehraban; Malahat Akbar Fahimi; Bahareh Maghfouri; Ali Reza Jamali (University of Social Welfare & Rehabilitation Sciences, 2019)
Objectives Older people are at risk of falling and its complications more than other age groups. Evaluation of environmental hazards requires time and money. So it seems necessary to design a self-report questionnaire for initial screening. This study aims to develop a self-report tool for falling risk assessment in Iranian older people. Methods & Materials After approval of the Ethics Committee of Iran University of Medical Sciences, an expert group prepared and wrote the study items using simple words and fluent structure. The reliability of the questionnaire was evaluated through test-retest method and its validity through content validity method. The elders were residents in their homes and had the appropriate level of consciousness to understand and respond to Persian sentences correctly. Information was collected through questionnaires and observations. Statistical evaluation was performed by SPSS version 16, and the retest test reliability of the questionnaire was determined by intra-class correlation coefficient. Results In terms of content validity, Content Validity Ratio (CVR) formula was used, and the agreement between the experts was significant, so the questionnaire has good content validity. Test-retest reliability was calculated by Standard Error of Mean (SEM), and relative and absolute repeatability coefficients showed excellent reliability of this questionnaire. The validity of the questionnaire was calculated based on the Spearman correlation coefficient of 0.95 and P value less than 0.001. The questionnaire contained 15 main questions and 75 sub-questions about the dangers of the home environment. Conclusion The results of this study showed high validity and reliability of this questionnaire, so it can be used as a practical tool for identifying the risks of falling at home.